Energy Harvesting from Simultaneous Galloping and Vortex-Induced Vibrations in a 2DOF System - Moussati, Youssef El; Hamdi, Mustapha; Belhaq, Mohamed (Journal of Vibration Testing and System Dynamics, 2026)
This paper investigates energy harvesting (EH) using simultaneous galloping and vortex-induced vibrations in a two-degree-of-freedom (2DOF) mechanical system coupled to an electrical circuit through an electromagnetic mechanism mounted on the secondary structure of the system. The main bluff body beam is subjected to aerodynamic forces, while the secondary beam is enclosed within the bluff body. The study compares two configurations. In the first configuration, the primary structure (with a bluff body) is submitted to a galloping aerodynamic force. In the second configuration, the primary structure is exposed simultaneously to galloping and vortex aerodynamic forces. The harmonic balance method (HBM) is applied to approximate the amplitude of vibrations and output power for the two configurations. Numerical simulations are performed to validate the analytical results. The energy harvested from both configurations is calculated and compared. The results show that combining galloping and vortex-induced vibrations enables the system to harvest higher energy at low wind speeds. This result may provide an optimization process that can be used to supply some guidelines in the design of galloping and vortex-induced vibrations-based electromagnetic energy harvesters.